On per-session end-to-end delay distributions and the call admission problem for real-time applications with QOS requirements. - Yates, David (Computer communication review.)
A crucial problem facing the designers and deployers of future high-speed networks is providing applications with quality of service (QOS) guarantees. For soft real-time applications, which are delay sensitive but loss tolerant, delay distribution is an important QOS measure of interest. In this paper we study (through simulation) the end-to-end delay distribution seen by individual sessions under simple first-come first-served (FCFS) multiplexing in a network model with two significant features: (1) all traffic is connection-oriented, (2) cross traffic along routes is representative of that seen by calls in a moderately sized wide area network (i.e., less than 100 switches). We compare these delay distributions with the worst case point-valued analytic delay bounds predicted by three different techniques for providing such bounds (two of which require a more sophisticated link-level scheduling policy). We also consider the per-hop delay distributions seen as a session progresses "deeper" into the network and determine the sensitivity of these delay distributions to the manner in which the interfering traffic is modeled. Finally, we use our delay distribution results to examine the tradeoff between the QOS requested by a call, the manner in which the QOS guarantee is provided, and the number of calls that are admitted at the requested QOS.